A Case Series: The Identification of Buried Bumper Syndrome With Abdominal Computed Tomography Scan in Two Severely Brain Injured Rehabilitation Patients. Issue 9 (20th February 2016) - Krull, Christine M.P.; Dennison, Andrew C.
Abstract: Buried bumper syndrome is a potentially dangerous complication related to percutaneous endoscopic gastrostomy tube placement. Early diagnosis of this condition is important to avoid further complications related to subcutaneous or intraperitoneal administration of tube feedings. However, diagnosis in persons with altered mental status due to brain injury is challenging because of the patient's lack of ability to communicate and report symptoms. We present 2 case studies that demonstrate both the importance of early diagnosis and management and the lack of adequate sensitivity of a Gastrografin‐aided kidney, ureter, and bladder (KUB) study.